Short Lecture "Consensus Statement: The Phytochemical Characterisation of Medicinal Plant Extracts (Conphymp) - from a Needs Assessment to the Defining Best Practice" - Echeverria-Morgado, J (GEORG THIEME VERLAG KG, 2022)
Sin Resumen Disponible